2010
DOI: 10.3732/ajb.0900287
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and causes of incongruence between plastid and nuclear Senecioneae (Asteraceae) phylogenies

Abstract: One of the longstanding questions in phylogenetic systematics is how to address incongruence among phylogenies obtained from multiple markers and how to determine the causes. This study presents a detailed analysis of incongruent patterns between plastid and ITS/ETS phylogenies of Tribe Senecioneae (Asteraceae). This approach revealed widespread and strongly supported incongruence, which complicates conclusions about evolutionary relationships at all taxonomic levels. The patterns of incongruence that were res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
212
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 228 publications
(249 citation statements)
references
References 87 publications
14
212
1
4
Order By: Relevance
“…As an internationally famous and reputable journal that publishes research on plant molecular phylogenetics, Systematic Botany was considered to be representative to some extent of the present status of cpDNA and nrDNA methodology. Given that some statistical methods for distinguishing hybridization from incomplete lineage sorting have only been published relatively recently [16,27,29], we restricted our search to the period between 2011 and 2005. The articles investigated had to fulfill the following two criteria: (i) one of the goals of the paper was to reconstruct phylogenetic relationships among members of a group or to determine the systematic position of a taxon, and (ii) the paper employed both cpDNA and nrDNA data to construct phylogenetic trees for the same taxa.…”
Section: Current Status Of Cpdna and Nrdna Data Analysis In Plant Phymentioning
confidence: 99%
See 2 more Smart Citations
“…As an internationally famous and reputable journal that publishes research on plant molecular phylogenetics, Systematic Botany was considered to be representative to some extent of the present status of cpDNA and nrDNA methodology. Given that some statistical methods for distinguishing hybridization from incomplete lineage sorting have only been published relatively recently [16,27,29], we restricted our search to the period between 2011 and 2005. The articles investigated had to fulfill the following two criteria: (i) one of the goals of the paper was to reconstruct phylogenetic relationships among members of a group or to determine the systematic position of a taxon, and (ii) the paper employed both cpDNA and nrDNA data to construct phylogenetic trees for the same taxa.…”
Section: Current Status Of Cpdna and Nrdna Data Analysis In Plant Phymentioning
confidence: 99%
“…However, it is sometimes extremely difficult to determine the cause of incongruence, particularly to distinguish hybridization from incomplete lineage sorting [28,29], which may result in similar phylogenetic patterns. Fortunately, several novel approaches have been developed for statistically distinguishing hybridization from incomplete lineage sorting [16,29].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Substitution model and best partitioning scheme were inferred using the program PartitionFinder v.1.1.1 ( Lanfear et al, 2012 ). Phylogenetic relationships were reconstructed using nrDNA and ptDNA separately, accounting for incongruence between the ptDNA and nrDNA data described earlier ( Pelser et al, 2007( Pelser et al, , 2010( Pelser et al, , 2012Calvo et al, 2013 ). Indels were coded for the plastid data only (Appendix S1 of the online Supplement).…”
Section: Methodsmentioning
confidence: 99%
“…Senecio has a nearly cosmopolitan distribution with major diversity centers in SA and South America ( Bremer, 1994 ;Pelser et al, 2007 ). Earlier molecular analyses and ancestral area reconstructions have shown that the genus is likely to have originated in sub-Saharan Africa in the mid to late Miocene, from where it dispersed to other parts of Africa and to all other continents except Antarctica ( Pelser et al, 2007( Pelser et al, , 2010( Pelser et al, , 2012. More specifi cally, we recently traced the origin of the genus to the dry or winter rainfall regions of western southern Africa (WSA) ( Kandziora et al, 2016 ).…”
mentioning
confidence: 99%